Political trust and legitimacy crisis in the age of COVID-19: an assessment of the EndSARS protest in Nigeria - Sanusi Gumbi, Khadijah; Baba, Yahaya T. (Frontiers in Political Science, 2024)
The article examined the manifestations of political trust deficits associated with people's response to policy choices of Nigeria's government during the COVID-19 pandemic. Like many other states, the African states and particularly the Nigerian government adopted WHO-recommended containment measures to limit the spread of the virus and the associated catastrophe. These measures included lockdowns, shutdowns, social distancing, and personal hygiene among other preventive procedures. Even though the pandemic was relatively less endemic in Africa, as per official statistics, African states swiftly implemented the WHO containment measures, which impacted negatively on the livelihood of the average household, who depends on daily incomes for survival. The worsening living condition caused by the containment measures expectedly deepened resentment against governments in Africa with already poor records of public service delivery, accountability, transparency, and human rights. Nigeria was one of the African countries that experienced citizens' backlash and violent outrage against government policy choices during the COVID-19. Under the guise fighting police brutality, youths staged mass anti-government protests that transformed into large scale violence, particularly in the southern parts of the country otherwise known as the “EndSARS Protests.” The protests were conceived against police brutality in the enforcement of COVID-19 measures. This article examined the outbreak of EndSARS protests as a transformation of the deepening of political trust deficits in age of COVID-19. It adopted qualitative approach using documentary evidence such as newspaper reports and official documents as instruments of data collection. The Institutional Performance Theory guided the article. The theory assumes that the actual performance of government determines citizens' level of trust and confidence in public institutions. The article found that perennial government inefficiency, limited accountability and transparency as well as poor human rights records of the government and its agencies, particularly the police exacerbated an already existing political trust deficits amongst the people in Nigeria. This was manifested in the outburst of a large-scale violent outrage by the youths as protest to the government containment measures and widespread dysfunctional governmental institutions and particularly police brutality. The article concluded that building trust is particularly important for governments, as this can be achieved through output sense, the provision of public goods, or social support.